Isolation And Characterization Of Rat Colonic Microflora For Targetting To Colon - P.ARULRAJ; R.SARASWATHY; CHANDHINI.R.NAIR; B.S.NATH; VSKM SUBRAMANYAM.M; R.VENKATNARAYANAN (International Journal of Pharma and Bio Sciences, 2010)
The increasing awareness of targeting the drug to specific site triggered us to evaluate the colonic content. We made an attempt to isolate and characterize the microbial flora present in the colon. We have isolated the ceacal content from the healthy rat and grown in the culture medium. Total characterization and preservation of the colonic microflora have been extensively studied. We reported here the gram type of bacteria, presence of flagella, catalase test, thermal death time, bacterial growth curve and bio chemical reactions such as methyl red test, citrate utilization test, voges proskauer test, also we reported that the ceacal matter should contain bacteriods in abundant. The characteristic information which is disclosed in this research would be more help full for targeting the drugs to colon.